Race & Prejudice: Constructing Race Identity in “The Help” Movie (2011) - Arfian Dwi Saputra; Gracia Petra Theresa; Happy Kurnia; Tedi Setyawan; Wahyu Rismayuda Dwitama; M. Afifulloh (UM Purwokerto Press, 2024)
This study aims to describe and analyse the representation of racism in the film